2017
DOI: 10.1371/journal.pone.0180941
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment strategies following Small Incision Lenticule Extraction (SMILE): In vivo tissue responses

Abstract: With any refractive correction, including Small Incision Lenticule Extraction (SMILE), there may be a residual refractive error that requires a retreatment. Here, we investigated the tissue responses following various retreatment procedures in a rabbit model of SMILE. All rabbits underwent a -6.00D correction with SMILE. Two weeks later, they underwent -1.00D enhancement by: (i) VisuMax Circle, followed by excimer ablation (S+C); (ii) secondary SMILE anterior to the primary procedure (S+SE); or (iii) surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…La presencia de activación de queratocitos es un hallazgo constante en cirugía refractiva con PRK, LASIK, Epi-LASIK y SMILE, debido a la cicatrización que presenta el estroma corneal, ya sea por el efecto del corte de la interfaz corneal como por la respuesta a la ablación del estroma mediante el láser excímer 8,9,[15][16][17][18] ; por tal motivo, es de esperar el hallazgo de activación de queratocitos en las porciones anterior y posterior a la interfaz corneal con la técnica de SMILE.…”
Section: Discussionunclassified
“…La presencia de activación de queratocitos es un hallazgo constante en cirugía refractiva con PRK, LASIK, Epi-LASIK y SMILE, debido a la cicatrización que presenta el estroma corneal, ya sea por el efecto del corte de la interfaz corneal como por la respuesta a la ablación del estroma mediante el láser excímer 8,9,[15][16][17][18] ; por tal motivo, es de esperar el hallazgo de activación de queratocitos en las porciones anterior y posterior a la interfaz corneal con la técnica de SMILE.…”
Section: Discussionunclassified
“…Extracellular matrix, including collagen, accumulates in keratinocytes, resulting in corneal opacity and increased thickness [12]. Some studies have shown that diagnostic ultrasound irradiation time can increase corneal apoptosis, which may lead to corneal opacity, thinning and bulge [13]. Some studies have shown that the intensity of ultrasound and the duration of irradiation will cause changes in the morphology of corneal tissue, a decrease in the level of corneal collagen, and corneal cells will experience apoptosis for a period of time; injured corneal cells will cause corneal epithelial cell apoptosis due to the accumulation of inflammatory cells, and chronic epithelial cell injury will lead to stroma thinning and epithelial hyperplasia [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the use of MMC in surface ablation retreatments is regarded as obligatory. Comparing reSMILE with CIRCLE retreatments, Riau et al 27 also found that CIRCLE showed more inflammatory and apoptotic cellular reactions than reSMILE in the early postoperative period. However, the response was mild, and MMC is not recommended as a routine treatment after CIRCLE.…”
Section: Enhancement Options From a Tissue Perspectivementioning
confidence: 99%
“…26 In the case of additional secondary treatments, these responses might however escalate in an disproportional manner. In an in vivo model in 15 New Zealand white rabbits, Riau et al 27 studied the different tissue responses in the early postoperative period after SMILE retreatment using anterior reSMILE, CIRCLE pattern D, and surface ablation. In comparison to reSMILE and CIRCLE, surface ablation caused the strongest tissue reaction with the highest amount of edema and haze.…”
Section: Enhancement Options From a Tissue Perspectivementioning
confidence: 99%